The umbrella movement : civil resistance and contentious space in Hong Kong - Ma, Ngok; Zheng, Wei (College teacher) (Global Asia (Amsterdam, Netherlands) ;, 2019)
For 79 days, the Umbrella Movement staged Hong Kong's most spectacular struggle for democracy. Sparked by disgruntlement over Beijing's denial of universal suffrage elections, the protests first began with class boycott along the largely-scripted Occupy Central, but later morphed into a spontaneous, resilient street occupation, transforming roads and pavements into protest sites and tent villages. Although the movement failed to bring any tangible political changes, it has transformed Hong Kong politics in many ways. Not only has it catalyzed the emergence of new movement agency, repertoires and claims, it has also defined a new era for Hong Kong, its relations with China and its identity in the world. This emerging political landscape merits thorough examination. This book is a collaborative attempt to examine this unprecedented and watershed event. It brings together 13 essays written by scholars with different disciplinary and research focuses. The chapters probe the political origins of the movement; identify new participants, protest forms and action repertoires; analyze protesters' strategies and regime responses; and also bring in comparative perspectives from mainland China, Taiwan and Macau. One common thread that stitches the chapters together is the use of first-hand data collected through on-site fieldwork across the protest sites.